Tinjauan Hukum terhadap Upaya Hukum Banding dan Kasasi dalam Perkara Perdata - Deni Maulana Ihsan; Rama Dwi Aryandhes; Muhammad Sulthan Rizqyansyah; Farahdinny Siswajanthy; Dinalara D. Butar Butar (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Appellate and cassation remedies play an important role in ensuring justice and legal certainty in civil cases in Indonesia. This research aims to review juridically related to procedures, legal basis, and challenges in the implementation of appeals and cassation. The method used is normative legal research with a qualitative approach, through data analysis from laws and regulations and court decisions. The results show that although these two legal remedies provide room for correction to court decisions, their implementation still faces obstacles, such as tight deadlines and limitations in submitting new evidence or discovery. In conclusion, the effectiveness of appeals and cassations is highly dependent on the understanding of procedures and the application of the principles of justice by a judicial institution. This research to be a reference for legal practitioners and academics in understanding the dynamics of civil legal remedies in Indonesia.